Peningkatan kemampuan membaca pemahaman menggunakan media e-flashcard pada siswa cerebral palsy kelas v di SLBN 1 Takalar - Meidina, Tatiana; Sulasminah, Dwiyatmi; Bastiana, Bastiana; Mubar, Muh. Maaris; Putri, Reza Sutarna (Trihayu: Jurnal Pendidikan Ke-SD-an, 2025)
In an effort to enhance the quality of learning services in Special Education Schools, it is essential to employ instructional media that are not only adaptive but also capable of providing stimulation aligned with the students’ individual characteristics. This study aimed to determine the effect of using e-flashcard media on improving the reading comprehension skills of a fifth-grade student with cerebral palsy at SLBN 1 Takalar. The research employed a Single Subject Research (SSR) design with an A1–B–A2 model, consisting of three phases: baseline 1 (A1), intervention (B), and baseline 2 (A2). Data were collected through direct observation of the subject’s reading comprehension performance across sessions. The within-condition analysis showed that during the A1 phase, data remained stable with no significant improvement, while during the intervention phase (B), reading comprehension increased with some variability. In the A2 phase, data became stable again, maintaining the same performance level as the final intervention sessions. The between-condition analysis revealed 0% overlap in both A1/B and B/A2 comparisons, indicating no data overlap between phases. These findings suggest that the use of e-flashcards effectively enhances and maintains reading comprehension skills in students with cerebral palsy. Therefore, e-flashcards can serve as an engaging and adaptive instructional strategy to support literacy learning among students with special needs.